KETERPAHAMAN BACAAN SISWA KELAS VI SD NEGERI NUSA TUNGGAL - Dwi Purnama Sari (Jurnal PGSD Musi, 2021)
This study aims to describe the reading understanding of the sixth grade student of SD Negeri Nusa Tunggal. This type research is a qualitative researh using desriptive method. Data collection techniques were carried out ussing the test procedure cloze as many as 5 readings were tested. The data analysis technique was carried qout using the test analysis procedure cloze in the form of a formula. The subjects in this study were all student of class VI SD Negeri Nusa Tunggal totaling 24 people. The results showed that the reading understanding of the sixth grade student of SD Negeri Nusa Tunggal was at the level of instruksional readers (medium). This is evidenced by the 5 readings tested, there are 3 readings that are at the level of instructional readers, namely, reading II as many as 13 students (54,16%), readings III as many as 16 (students (66,66%), and reading IV as many as students (45,83%) while 2 readings are at the level of frustrated readers, namely, reading I as many as 18 (75%), and reading V as many as 12 students (50%). This is evidenced from the percentage of student scores in table test results cloze showed the highest value cloze of each reading test. Thus, students reading ability in understanding reading is categorized as moderate or sufficient.